Prediction and Treatment of Water Leakage Risk Caused by the Dynamic Evolution of Ground Fissures in Gully Terrain - Feng, Dong; Hou, Enke; Xie, Xiaoshen; Che, Xiaoyang; Hou, Pengfei; Long, Tianwen (Frontiers in Earth Science, 2022)
Groundwater leakage in the loess gully terrain is one of the main hazards of coal seam mining at shallow burial depth. The burial depth of the 5−2 coal seam is less than 50 m from the ground in the gully of the study site. The fissures that expand upward after mining can easily penetrate the ground to form a water-conducting channels. During rainy periods, there is a potential risk of groundwater leakage. In order to reveal the characteristics of plane development and the dynamic evolution of gully ground fissures, the typical U-shaped gully in the northern Shaanxi coal mine was studied using the field measurement methods of “On-site measurement” and UAV aerial photography. Based on the experimental platform of ground fissure leakage developed and designed by the team, an indoor test model corresponding to the actual situation was established. In addition, the mathematical models of actual flood inrush, fissure width, and flood flow in the channel were established. The actual mine water flow and the mine drainage capacity were compared and analyzed, thus proposing criteria for classifying gully mining ground fissure collapsed water hazards. These criteria can provide theoretical references for predicting fissure leakage hazard zones in the ground gully of shallow buried coal seams. According to the development height of the water-conducting fissure zone (WCFZ), the treatment methods of ground fissures in gullies under different security conditions were designed, which was applied in the field with good results. The results showed that the treatment methods in this paper could effectively prevent the leakage of groundwater in the gullies along the ground fissures.